A synchronous spectrofluorometric technique for simultaneous detection of alfuzosin and tadalafil: applied to tablets and spiked biological samples - Heba Samir Elama; Shereen M. shalan; Yasser El-Shabrawy; Manal I. Eid; Abdallah M. Zeid (Royal Society Open Science, 2022)
A facile, accurate, eco-friendly and sensitive spectrofluorometric method was evolved to assay alfuzosin hydrochloride (AFH) and tadalafil (TDF) in different matrices. Such a co-administered combination is clinically used for the treatment of lower urinary tract symptoms. Both compounds are characterized by their native fluorescence spectra upon excitation at specific wavelengths. Their characteristic fluorescence spectra were used for sensitive assay of the studied analytes in tablets and human biological samples. The assay principle is based on first-order synchronous spectrofluorometric scan using Δλ = 60 nm in which AFH peaks were recorded at 366 nm. Meanwhile, TDF measurements were recorded at 293 nm in the same scans without overlap with AFH spectra. Recent analytical chemistry trends were implemented to lessen occupational and environmental perils, using ethanol as a diluting solvent for method optimization and application. Linearity ranges were 5.0–90.0 and 10.0–100.0 ng ml−1 for AFH and TDF, respectively in their raw materials with average % recoveries of 100.44% and 99.73% in raw materials, 100.15% and 100.20% in spiked plasma, and 97.14% and 99.99% in spiked urine. The proposed method was successfully applied to Prostetrol and Starkoprex commercial tablets with no interference with common tablet additives.